The Role of Motivation in Culture and the Arts - Hakimova Sadoqat Muhammadisoq kizi; Gulomova Muslima Ahmadillo kizi (Peerian Journals Publishing, 2022)
This article discusses the types of motivation that culture and the arts should be able to provide to students in the field of motivation.
Keywords: motivational professional training; social claim creative personality; spiritual need, sedentary activity; psychology